The tiger's apprentice [videorecording (DVD)] - Magee, David, 1962-; Yost, Christopher; Oh, Sandra, 1971-; Yep, Laurence, 1948- (Paramount, 2024)
In San Francisco's Chinatown, Tom discovers his family's legacy: they guard the phoenix egg, a powerful artifact that can either create or destroy. Stepping into this role, Tom teams up with a savvy tiger and zodiac warriors who can shift forms. Together, they dive into a high-stakes adventure, battling foes to protect the egg and uphold their family's honor.